Coastal Morphological Dynamics of Tangerang Regency Banten and Indah Kapuk Beach Jakarta through Google Earth Imagery Analysis - Endan Suwandana (Jurnal Perikanan dan Kelautan, 2019)
Tangerang Regency experienced very high coastal dynamic processes, caused by natural factors (abrasion and accretion) and anthropoligical factor (reclamation). This study aims to determine the latest condition of the Tangerang regency coastal dynamics as well as Pantai Indah Kapuk (PIK) area of Jakarta by using analysis of Google Earth images. The land area changing was calculated through visual interpretation approached by using on-screen digitizing. The applications used are Google Earth Pro 7.1.5.1557 and ArcGIS 10.2. Out of a total of 23 coastal villages, abrasion occurred in almost 20 villages. The highest abrasion phenomenon occurred in Kohod village, Pakuhaji district, with a land area lost of 71.55 ha during the 2004-2019 period. The highest accretion process occured at the estuary of the Cisadane river which was in Tanjungburung village, Teluknaga district. While the highest reclamation activity taken place in the village of Kosambi Timur with the total area of the reclaiming beach reached 56.54 ha. In both villages, Kosambi Timur and Dadap, District of Kosambi, the reclamation did not only occur at sea, but also on land. The area of fishponds that has been reclaimed and converted into the New Urban Zone of Pantura is about 936,78 ha. This is the largest fishpond conversion into a city ever happened in Indonesia. As a comparison, the conversion of aquaculture land to urban land had occurred previously in PIK Jakarta with the area of converted ponds around 678 ha.